Using computer technology to deliver nutrition education to low income populations - Gould, Susan Martin, author; Anderson, Jennifer, advisor; Chapman, Phillip, committee member; Auld, Garry, committee member; Kendall, Pat, committee member (Colorado State University. Libraries, 1997)
Nutrition education has been found to be effective in improving knowledge, attitudes, and behavior, particularly when programs are behavioral oriented and based on theoretical frameworks such as Prochaska's Stages of Change Model, the Social- Cognitive Leaming Theory, and the Communication Theory/Model. Increased nutrition risk has been found to be associated with income level, some minority groups, and education level. A nutrition education program, La Cocina Saludable ("The Healthy Kitchen"), has been developed utilizing abuelas (Hispanic grandmothers) to address some of the nutrition education needs of low-income Hispanic women and children, especially among migrant farm working families. Computer technology provides the opportunity to explore new and creative methods to deliver nutrition education to participants receiving food assistance. If this delivery method is effective, more people can be reached with accurate and consistent messages with less of the recruiting and training challenges found with peer educators. A pictorial version of the Colorado WIC Program Allowable Foods List was created using scanning and desk-top publishing techniques to add pictures and increase the readability of the text. Formative evaluation provided feedback regarding content and design. A final evaluation was completed to determine the preference between the text and pictorial versions. Potential WIC clients preferred the pictorial version (both Spanish and English) by more than 80%. Twelve of 14 grocery store checkers preferred using the pictorial version at their registers. Over 80% of 42 WIC staff surveyed indicated they would use the pictorial version more often with clients and that clients would like them. Building upon these scanning techniques, two units of La Cocina Saludable, "Make It Healthy" and "Make A Change," were adapted to a bilingual interactive multimedia (IMM) program and evaluated. The program was designed to be delivered via touch screen computers to participants of food and other assistance programs. Repeated measures analysis of variance (ANOVA) was used to assess the knowledge gains and reported behavior changes among participants who completed La Cocina Saludable with a computer and those who completed it with an abuela. Significant knowledge gains (p < 0.05) were observed with both methods of delivery. Those who received "Make It Healthy" with the abuela, however, had significantly more gains (p < 0.05) for that outcome than those who used the computer. No significant differences were seen between the abuela and IMM when comparing within the "Make A Change" unit. A few differences were reported for fat and salt behaviors. IMM provides an opportunity to expose more participants to accurate and consistent nutrition education messages and learning activities. Use of a combination of IMM and nutrition educator methods may be an important consideration to increase contacts and optimize gains.
Keywords: Nutrition -- Study and teaching; Poor -- Nutrition; Poor; Low budget cooking